KAJIAN PERILAKU WISATAWAN EROPA FIRST TIMER DAN REPEATER DI KELURAHAN UBUD - I Gede Gian Saputra; I Made Sukana (JURNAL DESTINASI PARIWISATA, 2013)
ABSTRACT European tourists who have a high interest in art and culture would be very appropriate for the tourism market of Ubud. Therefore, understanding the characteristics of European tourists is very important for the all stakeholders of Bali tourism, especially in relation to Ubud. This study aims to understand the meaning of behavior European first-timers and repeaters tourists who visited the village of Ubud. Studies of first timer and repeater tourist will be able to give a response why the tourists visit Ubud and what do they do there. In this study, the methods of data collection using observation, depth interviews, survey, and library research. While the techniques of data analysis using descriptive qualitative data analysis. Results obtained in this study were five of the most popular tourist activities by European tourists either first timers or repeaters. European first timers tourists are still in the position of "interest" and European repeater tourists in the position of "adoption" to perform their behavior in the Ubud Village.